DEBILIDADES EN LOS PROCESOS DE FACTURACIÓN Y RECETAS EN EL CENTRO DE SALUD ENRIQUE PONCE LUQUE DE LA CIUDAD DE BABAHOYO EGRESADA: LORENA ABIGAIL SÁCHEZ PEÑAFIEL TUTORA: Ing. MARÍA GENOVEVA MOREIRA SANTOS, MIE AÑO - SÁCHEZ PEÑAFIEL, LORENA ABIGAIL (2019)
Currently the computer systems are those that cover most of the activities, since these help us to avoid cumbersome processes and loss of time, and thus the quality of life has been improving, in the same way if you want to improve the processes, it is enough It is also essential to mention the lack of internal control of resources, and the lack of up-to-date training to put the health center at the forefront. There are companies that lack cutting-edge technologies or systems. that this depends on the welfare of society, that is why people have the concept that the services provided by certain entities are of poor quality and to some extent we have been able to see some shortcomings in this health center. In the present investigation we seek to determine the study of the difficulties within the processes of billing and the prescription of said health center, for the reason that several complaints and disagreement have been appearing among some individuals, and if this problem persists this It will mean that many people desist from receiving the services offered by the health house, this entity being one of the busiest within the city is of vital importance that everything is in optimal conditions from equipment, computer system, architecture, networks, etc. For this reason, a detailed analysis will be carried out so that the corresponding corrections can be determined in terms of billing phases and medical prescriptions, which is why the present case study is aimed at improving said drawbacks, proposing improvements and new ideas for so the Enrique Ponce Luque Health Center continues to provide the different services in an efficient, effective way and make it take much less time than before.